Evolution of the flux tube instability parameters in plasma injections at saturnian magnetosphere - Wing, Simon; Johnson, Jay R.; Thomsen, Michelle F.; Ma, Xuanye (Frontiers in Astronomy and Space Sciences, 2024)
The evolution of the flux tube stability parameters in plasma injections at the Saturnian magnetosphere is reviewed. Plasma injections result from an imbalance in the centrifugal, total pressure gradient, and magnetic tension forces acting on plasma in the magnetosphere. Plasma originating from Enceladus tends to move outward due to centrifugal forces while reconnected flux tubes that are depleted of plasma collapse because of the magnetic tension leading to plasma injections. As the flux tube moves inward and contracts, the ambient density and pressure increase sufficiently to resist further collapse and the injected flux tube brakes. During this process the flux tube may also lose its integrity due to particle drifts, which allow exchange of plasma with adjacent flux tubes so as to bring the flux tube closer to equilibrium and stability so that it is indistinguishable from adjacent plasma. Stability parameters using this energy approach are defined and examined. The results show that the net forces push the plasma moves inward for L > 11 and outward for L < 8.5, while equilibrium is generally reached for 8.5 < L < 11, where L is the equatorial magnetic field crossing measured in Saturnian radii. The evolution of the stability parameters can also apply to Jovian and other fast rotating planetary magnetospheres.